Perancangan Sistem Informasi Peminjaman pada Perpustakaan SMKN 5 Pekanbaru - Putra, Lindu Aji Dhiva; Windari, Hanisa Tri; Ningsih, Dwi Putri Wahyu; Rizal, Abid Muhammad; Hafiz, Muhammad; Winarso, Doni (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
A website is now a destination for crucial information in the contemporary digital era. Among the necessary educational resources for any school or institution are libraries. Because knowledge and information can be readily found by students at the library. People believe that as technology advances, they can operate more productively and successfully. Converting an analog system to an electronic one is one of them. By using the website Libraries that have internet access can operate more effectively and efficiently in carrying out bookkeeping. In this research, a web-based information system was designed using the PHP (Hypertext Preprocessor) programming language. The linear sequential research method was chosen because it is very suitable for projects with clear needs and limited resources and time. By creating It is hoped that this approach will be able to solve a number of issues. the need to look for books and facilitate the distribution of book loans and report writing for the school administration. Based on the findings of the conducted research, the author incorporated the study's findings into the creation of an online library information system SMKN 5 Pekanbaru library.